The effect of Ramadan fasting during pregnancy on perinatal outcomes: a systematic review and meta-analysis - Jocelyn D. Glazier; Dexter J. L. Hayes; Sabiha Hussain; Stephen W. D'Souza; Joanne Whitcombe; Alexander E. P. Heazell; Nick Ashton (BMC, 2018)
Abstract Background Although exempt, many pregnant Muslim women partake in the daily fast during daylight hours during the month of Ramadan. In other contexts an impoverished diet during pregnancy impacts on birth weight. The aim of this systematic review was to determine whether Ramadan fasting by pregnant women affects perinatal outcomes. Primary outcomes investigated were perinatal mortality, preterm birth and small for gestational age (SGA) infants. Secondary outcomes investigated were stillbirth, neonatal death, maternal death, hypertensive disorders of pregnancy, gestational diabetes, congenital abnormalities, serious neonatal morbidity, birth weight, preterm birth and placental weight. Methods Systematic review and meta-analysis of observational studies and randomised controlled trials was conducted in EMBASE, MEDLINE, CINAHL, Web of Science, Google Scholar, the Health Management Information Consortium and Applied Social Sciences Index and Abstracts. Studies from any year were eligible. Studies reporting predefined perinatal outcomes in pregnancies exposed to Ramadan fasting were included. Cohort studies with no comparator group or that considered fasting outside pregnancy were excluded, as were studies assuming fasting practice based solely upon family name. Quality of included studies was assessed using the ROBINS-I tool for assessing risk of bias in non-randomised studies. Analyses were performed in STATA. Results From 375 records, 22 studies of 31,374 pregnancies were included, of which 18,920 pregnancies were exposed to Ramadan fasting. Birth weight was reported in 21 studies and was not affected by maternal fasting (standardised mean difference [SMD] 0.03, 95% CI 0.00 to 0.05). Placental weight was significantly lower in fasting mothers (SMD -0.94, 95% CI -0.97 to  -0.90), although this observation was dominated by a single large study. No data were presented for perinatal mortality. Ramadan fasting had no effect on preterm delivery (odds ratio 0.99, 95% CI 0.72 to 1.37) based on 5600 pregnancies (1193 exposed to Ramadan fasting). Conclusions Ramadan fasting does not adversely affect birth weight although there is insufficient evidence regarding potential effects on other perinatal outcomes. Further studies are needed to accurately determine whether Ramadan fasting is associated with adverse maternal or neonatal outcome.